2009
DOI: 10.1111/j.1540-8167.2008.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Cardiac Sarcoid Mimicking Arrhythmogenic Right Ventricular Dysplasia

Abstract: In this prospective study of consecutive patients with suspected ARVD/C evaluated by a standard protocol including biopsy, the incidence of cardiac sarcoid was surprisingly high (15%). Clinical features, with the exception of left ventricular dysfunction and histological findings, did not discriminate between the two entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…Clinical features and electro- cardiographic findings are also similar to those in ARVC. Vasaiwala et al (45) showed that 15% of a group of 20 patients who were initially diagnosed with ARVC had sarcoidosis at endomyocardial biopsy. None of these patients had radiographic evidence of sarcoidosis.…”
Section: Pathologic Conditions That Mimic Findings In Arvc Sarcoidosismentioning
confidence: 99%
“…Clinical features and electro- cardiographic findings are also similar to those in ARVC. Vasaiwala et al (45) showed that 15% of a group of 20 patients who were initially diagnosed with ARVC had sarcoidosis at endomyocardial biopsy. None of these patients had radiographic evidence of sarcoidosis.…”
Section: Pathologic Conditions That Mimic Findings In Arvc Sarcoidosismentioning
confidence: 99%
“…Nearly all patients have predominant LV disease. However, since 2003, 16 cases of RV sarcoidosis mimicking ARVC have been described (Table I), [1][2][3][4][5][6][7][8][9][10][11][12] and only 2 patients had isolated RV involvement. 1,6 Our patient had a similar uncommon presentation of cardiac sarcoidosis with isolated RV involvement and LV-sparing that clinically mimicked ARVC.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is confirmed by EMB and thoracic CT scans. 151 DCM is particularly difficult to distinguish from non-classic forms of ACM, and these two entities can significantly overlap and harbour similar mutations. Palpitations, (pre)syncope and ventricular arrhythmias are present at an early stage in ACM, often in the absence of gross structural abnormalities, which is the opposite in DCM.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In a study of patients with suspected ARVC/D also being evaluated by EMB, a high incidence (15 %) of cardiac sarcoid was identified. 151 Cardiac sarcoid should be considered if respiratory and systemic symptoms, high-grade atrioventricular conduction block and septal involvement are present, and familial disease is absent. Diagnosis is confirmed by EMB and thoracic CT scans.…”
Section: Differential Diagnosismentioning
confidence: 99%